The Implementation of Childhood Obesity Related Policy Interventions in Malaysia—A Non Communicable Diseases Scorecard Project - Mok, Wilfred Kok Hoe (Int J Environ Res Public Health, 2021)
(1) Background: The prevalence of overweight and obesity among children has increased tremendously in the ASEAN region, including Malaysia. In Malaysia, the National Strategic Plan for Non-Communicable Diseases (2015–2025) provides the overall framework for its response to the non-communicable diseases (NCD) epidemic. Preventing childhood obesity is one of the key strategies for early intervention to prevent NCDs. The objective of this research is to examine the current status of policy interventions in addressing childhood obesity in Malaysia. (2) Methods: A panel of 22 stakeholders and experts from Malaysia, representing the government, industry, academia and non-governmental organizations, were sampled using a modified Delphi technique. Data were collected using a modified NCD scorecard under four domains (governance, risk factors, surveillance and research and health systems response). A heat map was used to measure the success of the four realms of the NCD scorecard. For each domain of the NCD scorecard, the final score was grouped in quintiles. (3) Results: A total of 22 participants responded, comprising of eight (36.4%) males and 14 (63.4%) females. All the domains measured in implementing policies related to childhood obesity were of low progress. Nine governance indicators were reported as 22.5% (low progress), four in the risk factors domain, and two in the surveillance. This shows that timely and accurate monitoring, participatory review and evaluation, and effective remedies are necessary for a country’s surveillance system. (4) Conclusion: Although Malaysia has published several key strategic documents relating to childhood obesity and implemented numerous policy interventions, we have identified several gaps that must be addressed to leverage the whole-of-government and whole-of-society approach in addressing childhood obesity in the country.